HUBUNGAN PENDIDIKAN DAN KEPERCAYAAN DENGAN STIGMA TOKOH AGAMA TERHADAP ORANG DENGAN HIV/AIDS (ODHA) DI KABUPATEN BANYUMAS - Retnowati, Misrina (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The development of Human Immunodeficiency Virus (HIV) and Acquired Immune Deficiency Syndrome (AIDS) problems are increasingly worrisome both from both quantitative and qualitative perspectives. HIV / AIDS prevention policies and programs have been widely implemented in Indonesia, but their implementation is still constrained. These constraints include socio-cultural aspects including stigma and discrimination.Â The problems of stigma and discrimination against towards people with HIV/AIDSÂ  should be addressed so that HIV / AIDS prevention and prevention activities can be effectively implemented. One way to do this is to involve religious leaders to help inform the public about HIV / AIDS issues. The objective of the study was to describe education, trust and stigma of religion towards people with HIV/AIDS. Know the relationship of education and trust with the stigma of religion towards people with HIV/AIDS.Â The research method is correlational analytic research with cross sectional approach. The population is all religious leaders in Banyumas Regency with 278 people, with a sample of 164 people taken proportional random sampling. The results of the study most of the middle educated respondents as much as 83.5%, some respondents had less trust about HIV / AIDS as much as 50.6% and most respondents stigmatized people with HIV / AIDS by 55.5%. There is a relationship of trust with stigma of religion towards people with HIV/AIDS with Ï value 0.009 and There is no relationship of education with stigma of religion towards people with HIV/AIDS with Ï value 0.401 .Â Conclusion there is a relationship of trust with stigma of religion towards people with HIV/AIDS and there is no relationship of education with stigma of religion towards people with HIV/AIDS.Keywords: Education, Trust, Stigma of Religion towards People with HIV / AIDS